Faktor-Faktor yang Memengaruhi Pemanfaatan Posyandu Lansia dengan Pendekatan Model Sistem Pelayanan Kesehatan - Ngatoiatu Rohmani; Ferianto Ferianto; Satria Kustiawan; Elvira La Bula (Jurnal Indonesia Sehat, 2022)
Background:  Integrated Service Posts (Posyandu) Elderly is a place for health services for the elderly that are formed and driven by the community in collaboration with the Puskesmas by focusing on promotive and preventive efforts. Unfortunately, the use of the elderly posyandu program by the community is not yet optimal. The participation and activeness of the elderly in the program is still less than 80%. Purpose:  Through the health service system model, this study aims to analyze the affecting factors on the utilization of posyandu for the elderly. Method:  This study was quantitative, using descriptive analytic design with cross sectional approach. The respondents are elderly residents of Balecatur Village, Gamping. 59 sample was obtained by purposive sampling technique. Data collection using a questionnaire and analyzed using a logistic regression test. Result:  showed that 32 respondents (54.2%) use of posyandu well. Chi-square test results found that the use of posyandu is related to the performance of cadres (p = 0.011). While the logistic regression results showed that the use of posyandu is influenced by the performance of the cadres (p = 0.001, OR = 1,231) and facilities and infrastructure (p = 0.004, OR = 0.115). Conclusion:  Cadre performance is the most dominant factor influencing the utilization of elderly Posyandu.